Is there a future for sequential chemical extraction? - Bacon, Jeffrey R.; Davidson, Christine M. (Analyst (London), 2008)
Since their introduction in the late 1970s, sequential extraction procedures have experienced a rapid increase in use. They are now applied for a large number of potentially toxic elements in a wide range of sample types. This review uses evidence from the literature to consider the usefulness and limitations of sequential extraction and thereby to assess its future role in environmental chemical analysis. It is not the intention to provide a comprehensive survey of all applications of sequential extractions or to consider the merits and disadvantages of individual schemes. These aspects have been covered adequately in other, recent reviews. This review focuses in particular on various key issues surrounding sequential extractions such as nomenclature, methodologies, presentation of data and interpretation of data, and discusses typical applications from the recent literature for which sequential extraction can provide useful and meaningful information. Also covered are emerging developments such as accelerated procedures using ultrasound- or microwave energy-assisted extractions, dynamic extractions, the use of chemometrics, the combination of sequential extraction with isotope analysis, and the extension of the approach to non-traditional analytes such as arsenic, mercury, selenium and radionuclides.